In vivo self-association of the Drosophila rel-protein dorsal. - Govind, S.; Whalen, A.M.; Steward, R. (Proceedings of the National Academy of Sciences of the United States of America, 1992)
The Drosophila morphogen dorsal, KBF1, NF-kappa B, and the proto-oncogene c-rel belong to the rel family of transcription factors whose function is regulated post-translationally by selective nuclear import. In the early Drosophila embryo, dorsal protein is proposed to be retained in the cytoplasm through its interaction with cactus protein. The maternal dorsal group genes constitute a signal transduction pathway, which results in targeting cytoplasmic dorsal protein into the nuclei of the syncytial blastoderm embryo, in a ventral-to-dorsal gradient. The asymmetric transcriptional regulation of zygotic genes along the dorsoventral axis by the dorsal morphogen gradient establishes embryonic dorsoventral polarity. In the lymphocytes, the functional equivalent of cactus is I kappa B, which appears to retain NF-kappa B in the cytoplasm. This retention is relieved by extracellular signals in tissue culture. NF-kappa B and rel proteins each are known to function as oligomeric complexes. Here we present genetic and biochemical evidence for the existence and functional importance of an oligomeric dorsal complex in vivo.